2020
DOI: 10.1007/s41887-020-00060-1
|View full text |Cite|
|
Sign up to set email alerts
|

Highest Harm Crime “Recruiters” in a London Borough: a Case of Moving Targets

Abstract: Research Question Can criminal recruiters be identified and ranked by crime harm levels in a London borough, and if so, how long is the predictive window of opportunity for targeting them with crime prevention efforts? Data This study deploys 5 years of Metropolitan Police Service crime data, relating to one of the 32 London boroughs in that time period. The data structure allowed identification of all suspects linked to the same crime report and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The Danish CHI follows the same methodology as other CHI models worldwide (see variations and applications in Ariel et al ., 2016; Basford et al ., 2021; Bland et al ., 2021; Curtis-Ham, 2022; Curtis-Ham and Walton, 2017, 2018; Dudfield et al ., 2017; House and Neyroud, 2018; Kärrholm et al. , 2020; Linton and Ariel, 2020; Macbeth and Ariel, 2019; Mitchell, 2019; Ohyama et al ., 2022; Ransley et al ., 2018; Sidhu et al ., 2017; Šimon and Jíchová, 2020; Weinborn et al ., 2017) and is considered an objective and valid measure of crime harm (however, cf. Sarnecki, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Danish CHI follows the same methodology as other CHI models worldwide (see variations and applications in Ariel et al ., 2016; Basford et al ., 2021; Bland et al ., 2021; Curtis-Ham, 2022; Curtis-Ham and Walton, 2017, 2018; Dudfield et al ., 2017; House and Neyroud, 2018; Kärrholm et al. , 2020; Linton and Ariel, 2020; Macbeth and Ariel, 2019; Mitchell, 2019; Ohyama et al ., 2022; Ransley et al ., 2018; Sidhu et al ., 2017; Šimon and Jíchová, 2020; Weinborn et al ., 2017) and is considered an objective and valid measure of crime harm (however, cf. Sarnecki, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The CHI assigns each crime category a harm score based on the Danish sentencing guidelines (the guidance to prosecutors and judges as to the recommended number of prison days first-time offenders should receive if the case were to progress to PIJPSM 46,2 court). The Danish CHI follows the same methodology as other CHI models worldwide (see variations and applications in Ariel et al, 2016;Basford et al, 2021;Bland et al, 2021;Curtis-Ham, 2022;Curtis-Ham andWalton, 2017, 2018;Dudfield et al, 2017;House and Neyroud, 2018;K€ arrholm et al, 2020;Linton and Ariel, 2020;Macbeth and Ariel, 2019;Mitchell, 2019;Ohyama et al, 2022;Ransley et al, 2018;Sidhu et al, 2017;Simon and J ıchov a, 2020;Weinborn et al, 2017) and is considered an objective and valid measure of crime harm (however, cf. Sarnecki, 2021).…”
Section: Measurementsmentioning
confidence: 99%
“…Crime data were then coded against the Cambridge Crime Harm Index (CCHI; Sherman et al, 2016). CCHI and versions of CCHI are a recent though established metric that has been used in multiple studies for tracking harm (Ariel et al, 2016;Bland & Ariel, 2015, 2020Barnham et al, 2017;Dudfield et al, 2017;House & Neyroud, 2018;Linton & Ariel, 2020a, 2020bMitchell, 2019;Weinborn et al, 2017;Weir et al, 2019; however, see critique in Sarnecki, 2021). The index assigns a value to each classification of crime based on official guidelines for starting point sentences for first convictions with no aggravating factors.…”
Section: Crime Harmmentioning
confidence: 99%
“…If they consented, the case was then randomly allocated to either the caution or Pathfinder arm of the trial. Randomisation was conducted using an online calculator (Ariel et al, 2012;Linton & Ariel, 2020a, 2020b, as shown in Fig. 1.…”
Section: Random Allocationmentioning
confidence: 99%